1994
DOI: 10.1203/00006450-199404000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-four-Hour Osteocalcin, Carboxyterminal Propeptide of Type I Procollagen, and Aminoterminal Propeptide of Type III Procollagen Rhythms in Normal and Growth-Retarded Children

Abstract: ABSTRACf. The relationships between spontaneous variations in serum 24-h osteocalcin (DC), carboxyterminal propeptide of type I procollagen (PICP), and aminoterminal propeptide of type III procollagen (PIIINP) concentrations and GH secretion, measured as GH response to provocative pharmacologic stimuli and spontaneous GH secretion during 24 h, were evaluated in prepubertal normal children and in GH-deficient and GH-secreting short normal children (SNC). All the subjects showed a circadian rhythm in smoothed 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
22
1
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 25 publications
(53 reference statements)
4
22
1
1
Order By: Relevance
“…Osteocalcin, a sensitive bone formation marker, was reported previously in adults and children to have a zenith at night and nadir in the morning (17,18). In the present study, a similar nocturnal zenith in plasma osteocalcin was observed in infant piglets.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Osteocalcin, a sensitive bone formation marker, was reported previously in adults and children to have a zenith at night and nadir in the morning (17,18). In the present study, a similar nocturnal zenith in plasma osteocalcin was observed in infant piglets.…”
Section: Discussionsupporting
confidence: 75%
“…A circadian rhythm in bone formation has been reported in adults and children, with a zenith at night and nadir in the morning (17,18). Circadian rhythm in bone formation has not been assessed in infants; possibly because of the difficulty of collecting serial blood samples from newborn infants.…”
mentioning
confidence: 99%
“…Indeed, OC, PICP, and ICTP levels follow a similar circadian rhythm with peak values occurring in early morning and nadirs in the afternoon (1,30,37). Circadian variation in bone markers appears to be unaffected by age and sex (38), as well as by growth and ageing (39).…”
Section: Discussionmentioning
confidence: 93%
“…In any case, the diminished somatic growth likely contributed to reducing the levels of the bone markers. In this context, we have demonstrated that 24-h PICP but not 24-h OC concentrations were growth velocity-dependent and GH-dependent in children with GHD (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation